Gap Measurements in Aerospace Engineering - Xinyuan Zhao; Chao Zhang; Long Xu; Tao Wang; Pei Li; Heng Zhang; Jun Yang (Sensors)
Advanced precision gap measurement technologies play a pivotal role in ensuring the design and operational efficiency of aerospace systems. Gaps between aircraft components directly influence assembly accuracy, performance, and safety. This review comprehensively explores the state-of-the-art in precision gap measurement technologies used in the aerospace sector. It categorizes and analyzes various sensors based on their operating principles, including optical, electrical, and other emerging technologies. Each sensor’s principle of operation, key advantages, and limitations are detailed. Furthermore, the paper identifies the significant challenges faced in aerospace gap measurement and discusses future development directions, emphasizing the need for enhanced accuracy, adaptability, and resilience to environmental factors. This study provides valuable insights for researchers and engineers in the field, guiding future innovations in precision gap measurement technologies to meet the evolving demands of aerospace manufacturing and maintenance.